PENGARUH LOKASI DAN HARGA TERHADAP KEPUTUSAN MEMILIH INDRALOKA HOMESTAY SERTA DAMPAKNYA TERHADAP LOYALITAS - Ambar Lukitaningsih (JURNAL EKONOMI DAN KEWIRAUSAHAAN, 2019)
The purpose of this study is to determine the Influence of Price and Location on buying decision of Indraloka Homestay and its impact on Loyalty. This research is done by quantitative method. The study population included all guests who had stayed at Indraloka Homestay with 80 respondents. The unit of analysis of this study are individuals who understand the substance of research obtained as a sample by using purposive sampling technique. expected data obtained will be relevant to the research problem. The analytical tool used Smart Partial Least Square (SmartPLS). The results showed that the variable price and location have a significant influence on Purchase Decision, Price has a significant influence on Customer Loyalty, Location has no significant effect on Customer Loyalty, Purchase Decision has a significant influence on Customer Loyalty.Keywords: price, location, buying decision, loyalty